Soufeng sanjie formula alleviates collagen-induced arthritis in mice by inhibiting Th17 cell differentiation - Di Hua; Jie Yang; Qinghai Meng; Yuanyuan Ling; Qin Wei; Zhigang Wang; Qingyun Wei; Jiao Chen; Juan Ye; Xuan Han; Kelei Su; Weikang Kong; et al. (BMC, 2021)
Abstract Background Rheumatoid arthritis (RA) is a chronic autoimmune disease. Soufeng sanjie formula (SF), which is composed of scolopendra (dried body of Scolopendra subspinipes mutilans L. Koch), scorpion (dried body of Buthus martensii Karsch), astragali radix (dried root of Astragalus membranaceus (Fisch.) Bge), and black soybean seed coats (seed coats of Glycine max (L.) Merr), is a traditional Chinese prescription for treating RA. However, the mechanism of SF in treating RA remains unclear. This study was aim to investigate the anti-arthritic effects of SF in a collagen-induced arthritis (CIA) mouse model and explore the mechanism by which SF alleviates arthritis in CIA mice. Methods For in vivo studies, female DBA/1J mice were used to establish the CIA model, and either SF (183 or 550 mg/kg/day) or methotrexate (MTX, 920 mg/kg, twice/week) was orally administered to the mice from the day of arthritis onset. After administration for 30 days, degree of ankle joint destruction and serum levels of IgG and inflammatory cytokines were determined. The balance of Th17/Treg cells in the spleen and lymph nodes was analyzed using flow cytometry. Moreover, the expression levels of retinoic acid receptor-related orphan nuclear receptor (ROR) γt and phosphorylated STAT3 (pSTAT3, Tyr705) in the spleen were detected by immunohistochemistry. Furthermore, the effect of SF on Th17 cells differentiation in vitro was investigated in CD4+ T cells under Th17 polarization conditions. Results SF decreased the arthritis score, ameliorated paw swelling, and reduced cartilage loss in the joint of CIA mice. In addition, SF decreased the levels of bovine collagen-specific IgG in sera of CIA mice. SF decreased the levels of inflammatory cytokines (TNF-α, IL-6, and IL-17A) and increased the level of IL-10 both in the sera and the joint of CIA mice. Moreover, SF treatment rebalanced the Th17/Treg ratio in the spleen and lymph nodes of CIA mice. SF also reduced the expression levels of ROR γt and pSTAT3 (Tyr705) in the spleen of CIA mice. In vitro, SF treatment reduced Th17 cell generation and IL-17A production and inhibited the expression of RORγt, IRF4, IL-17A, and pSTAT3 (Tyr705) under Th17 polarization conditions. Conclusions Our results suggest that SF exhibits anti-arthritic effects and restores Th17/Treg homeostasis in CIA mice by inhibiting Th17 cell differentiation.